Hydrogen Sulfide Generated by l-Cysteine Desulfhydrase Acts Upstream of Nitric Oxide to Modulate Abscisic Acid-Dependent Stomatal Closure . Issue 4 (29th September 2014) - Scuffi, Denise; Álvarez, Consolación; Laspina, Natalia; Gotor, Cecilia; Lamattina, Lorenzo; García-Mata, Carlos
Abstract : An l -cysteine desulfhydrase is a unique component of ABA signaling in guard cells, mediating H2 S production and acting upstream of nitric oxide to induce stomatal closure . Abstract: Abscisic acid (ABA ) is a well-studied regulator of stomatal movement. Hydrogen sulfide (H2 S ), a small signaling gas molecule involved in key physiological processes in mammals, has been recently reported as a new component of the ABA signaling network in stomatal guard cells. In Arabidopsis ( Arabidopsis thaliana ), H2 S is enzymatically produced in the cytosol through the activity of l -cysteine desulfhydrase (DES1). In this work, we used DES1 knockout Arabidopsis mutant plants ( des1 ) to study the participation of DES1 in the cross talk between H2 S and nitric oxide (NO ) in the ABA -dependent signaling network in guard cells. The results show that ABA did not close the stomata in isolated epidermal strips of des1 mutants, an effect that was restored by the application of exogenous H2 S . Quantitative reverse transcription polymerase chain reaction analysis demonstrated that ABA induces DES1 expression in guard cell-enriched RNA extracts from wild-type Arabidopsis plants. Furthermore, stomata from isolated epidermal strips of Arabidopsis ABA receptor mutant pyrabactin-resistant1 ( pyr1 )/ pyrabactin-like1 ( pyl1 )/ pyl2 / pyl4 close in response to exogenous H2 S, suggesting that this gasotransmitter is acting downstream, although acting independently of the ABA receptor cannot be ruled out with this data. However, the Arabidopsis clade-A PROTEIN PHOSPHATASE2C mutant abscisic acid-insensitive1 ( abi1-1 ) does not close the stomata when epidermal strips were treated with H2 S, suggesting that H2 S required a functional ABI1. Further studies to unravel the cross talk between H2 S and NO indicate that (1) H2 S promotes NO production, (2) DES1 is required for ABA -dependent NO production, and (3) NO is downstream of H2 S in ABA -induced stomatal closure. Altogether, data indicate that DES1 is a unique component of ABA signaling in guard cells.